Bayonet Fencing : An overview of historiography and techniques for French footmen during World War I - Julien Garry (Bern Open Publishing, 2021)
This article addresses the evolution of French bayonet fencing, teachings and methods over the course of World War I, under both historiographical and technical approaches. After a brief summary of the existent methods at the start of the War, we will explore the evolutions underwent by this Martial Art, brought by the changing nature and warfare and the various inputs of experienced fighter.